2007
DOI: 10.1002/ana.21143
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic study of autosomal recessive cerebellar ataxia type 1

Abstract: We identified a cluster of French-Canadian families with a new recessive ataxia of relatively pure cerebellar type caused by mutations in SYNE1. The function of SYNE1 is thus critical in the maintenance of cerebellar structure in humans. We expect that this disease will be a common cause of middle-age-onset recessive ataxia worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 13 publications
(19 reference statements)
1
34
1
1
Order By: Relevance
“…Contrary to the latter findings, our results suggest that pure, severe and diffuse cerebellar atrophy is associated with significant and specific cognitive changes. As described in earlier reports, ARCA-1 is a new recessive pure cerebellar ataxia that is caused by mutations in SYNE1 [21,22]. It shows relative homogeneity of the phenotype, despite being caused by more than seven different mutations.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Contrary to the latter findings, our results suggest that pure, severe and diffuse cerebellar atrophy is associated with significant and specific cognitive changes. As described in earlier reports, ARCA-1 is a new recessive pure cerebellar ataxia that is caused by mutations in SYNE1 [21,22]. It shows relative homogeneity of the phenotype, despite being caused by more than seven different mutations.…”
Section: Discussionmentioning
confidence: 70%
“…All affected family members have a similar phenotype, which consists of a late-onset (mid-thirties) pure cerebellar ataxia with slow progression. This new disease entity has been named autosomal recessive cerebellar ataxia type 1 (ARCA-1) or recessive ataxia of Beauce [21,22] and is caused by mutations in the SYNE1 gene. ARCA-1 represents a unique model to explore the role of the cerebellum in cognition because all patients show diffuse severe cerebellar atrophy without involvement of other areas of the central or peripheral nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Dupre et al [27] have identified a patient population with a pure cerebellar ataxia that has diffuse atrophy throughout the cerebellum with no additional abnormalities in the central or peripheral nervous systems. This form of ataxia has been termed autosomal recessive cerebellar ataxia type 1 (ARCA-1, or recessive ataxia of Beauce), which is caused by mutations in the SYNE-1 gene.…”
Section: Introductionmentioning
confidence: 99%
“…This form of ataxia has been termed autosomal recessive cerebellar ataxia type 1 (ARCA-1, or recessive ataxia of Beauce), which is caused by mutations in the SYNE-1 gene. This is an inherited cerebellar ataxia with an onset at middle age progressing slowly and leading to a moderate level of disability [27,28]. In order to better understand the cerebellar contributions to locomotor coordination, the cerebellar ataxia participants recruited in this study were all identified as having ARCA-1 with confirmed mutations in the SYNE-1 gene.…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of the sporadic adult-onset ataxias begin considerably later [ 22 ], so it is questionable if ARCA1 accounts for many of the sporadic ataxia cases. The seven point mutations described so far do not differ in clinical presentation [ 23 ]. All affect proper splicing, which results in truncation of the large protein of greater than 1000 kD that is expressed in multiple tissues, with predominant expression in cerebellar neurons.…”
Section: New Loci/new Genesmentioning
confidence: 97%